Combined small RNA and degradome sequencing to identify miRNAs and their targets in response to drought in foxtail millet. Issue 1 (December 2016) - Wang, Yongqiang; Li, Lin; Tang, Sha; Liu, Jianguang; Zhang, Hanshuang; Zhi, Hui; Jia, Guanqing; Diao, Xianmin
Abstract Background Foxtail millet (Setaria italica ) is a diploid C4 panicoid species. Because of its prominent drought resistance, small genome size, self-pollination, and short life cycle, foxtail millet has become an ideal model system for studying drought tolerance of crops. MicroRNAs (miRNAs) are endogenous, small RNAs that play important regulatory roles in the development and stress response in plants. Results In this study, we applied Illumina sequencing to systematically investigate the drought-responsive miRNAs derived fromS. italica inbred An04-4783 seedlings grown under control and drought conditions. Degradome sequencing was applied to confirm the targets of these miRNAs at a global level. A total of 81 known miRNAs belonging to 28 families were identified, among which 14 miRNAs were upregulated and four were downregulated in response to drought. In addition, 72 potential novel miRNAs were identified, three of which were differentially expressed under drought conditions. Degradome sequencing analysis showed that 56 and 26 genes were identified as targets of known and novel miRNAs, respectively. Conclusions Our analysis revealed post-transcriptional remodeling of cell development, transcription factors, ABA signaling, and cellar homeostasis inS.italica in response to drought. This preliminary characterization provided useful information for further studies on the regulatory networks of drought-responsive miRNAs in foxtail millet.